Analytical Research on Indicators of Sustainable Development Objectives in Uzbekistan - Safarova Dilshodaxon Eshmuxammadovna (Scientific Trends, 2024)
This study focuses on examining the indicators associated with sustainable development goals (SDGs) in Uzbekistan. By analyzing statistical data, the research aims to assess the progress the country has made toward achieving these goals. Special attention is given to the various indicators that reflect environmental, social, and economic dimensions of sustainability. The investigation utilizes a comprehensive set of data to evaluate both strengths and weaknesses in the current framework. Furthermore, it identifies areas that require targeted interventions to enhance overall effectiveness in reaching the SDGs. The findings of this analysis hold significant implications for policymakers, as they can guide future strategies and initiatives geared toward sustainable development in Uzbekistan. The study underlines the importance of systematic data collection and analysis in order to facilitate informed decision-making and foster a sustainable future for the nation. By providing a clearer picture of the existing landscape, this research can contribute to effective policy formulation and implementation in line with global sustainability goals.
Keywords: Sustainable Development Goals statistics, education, gender equality, clean water and sanitation, energy, economic growth, and sustainable cities.